CO2 emissions and soil carbon mineralisation under different systems1 = Emissões de CO2 e mineralização do carbono do solo sob diferentes sistemas - Auler, André Carlos; Hennipman, Hagata Siqueira; Jacques, Filipe Lemos; Romaniw, Jucimare; Charnobay, Aghata Cristie Rewa (Agro@mbiente on-line, 2019)
Usage and management alter the dynamics of soil organic carbon (SOC). The aim of this study was to compare the CO2 emissions in a Typic Humudept under different uses, and to relate the effects of CO2 emissions to the organic carbon content of the soil. Soil samples were collected from the 0-0.05, 0.05-0.10, 0.10-0.15 and 0.15-0.20 m layers under the following agricultural systems: no-tillage (NT), conventional (CT) and fruit orchard (FO). Samples were also collected from an area of native forest (NF) adopted as reference. The variables under evaluation were CO2 emissions and SOC content. Interaction between the usage or management systems and the soil layers influenced CO2 emissions in the soil. However, there was a difference in CO2 emissions between the soil layers under NF and CT only. In the 0-0.20 m layer, there was no difference in CO2 emissions under FO or CT, however these were greater than under NF or NT. In turn, the emissions under NT were lower than under NF at this layer. Furthermore, the systems with greater CO2 emissions showed less SOC. As such, in a Typic Humudept, the no-tillage management system results in reduced CO2 emissions. Greater SOC mineralisation has a direct impact on higher CO2 emissions. = O uso e o manejo alteram a dinmica do carbono orgnico no solo (COS). Neste contexto, objetivou-se com este trabalho comparar a emissão de CO2 de um Cambissolo Húmico Tb distrófico típico sob distintos usos e relacionar os efeitos da emissão de CO2 com o conteúdo de carbono orgnico do solo. Para isso, foram coletadas amostras de solo nas camadas de 0-0,05, 0,05-0,10, 0,10-0,15 e 0,15-0,20 m sob os sistemas agrícolas: plantio direto (SPD), convencional (SC) e pomar de frutíferas (PF). Também foram coletadas amostras de uma área de mata nativa (MN), adotada como referência. Foram avaliadas as variáveis: emissão de CO2 e conteúdo de COS. A interação entre os sistemas de uso ou manejo e as camadas do solo influenciaram a emissão de CO2 no solo. No entanto, houve distinção na emissão de CO2 entre as camadas de solo apenas na MN e SC. Na camada de 0-0.20 m, a emissão de CO2 do PF e SC não diferiram entre si, porém foram superiores a MN e ao SPD. Por sua vez, a emissão do SPD foi inferior à da MN nessa camada. Ainda, os sistemas com maior emissão de CO2 apresentaram menor COS. Assim, no Cambissolo Húmico Tb distrófico típico, o sistema de plantio direto é o manejo de solo que proporciona menores emissões de CO2. A maior mineralização do COS repercute diretamente em uma maior emissão de CO2.